Energy Citizenship - Dunphy, Niall P.; Lennon, Breffní; Revez, Alexandra; Pearce, Bin Bin J. (Springer Nature, 2025)
This open access book develops a deeper understanding of an increasingly applied term across policy cycles and academic discourses, ‘energy citizenship’. It provides the reader with five distinct chapters, with each in turn examining a specific aspect of the concept and how it has manifested in public discourses.